Forensic Estimation of Stature from Foot Length: An Autopsy based Study - Sheik Shakeer Hussain S; Sheeju P.A.; Ajay Balachandran (Indian Journal of Forensic Medicine & Toxicology, 2021)
The present study was conducted on 224 dead bodies of Keralites (167 males and 57 females) aged between20 and 60 years. The correlation coefficient calculated in males for the stature and right foot length (0.779)and left foot length (0.778); and the right foot length (0.653) and left foot length (0.638) in females weresignificant at 0.01 level. Males had significantly higher mean values for both stature and foot length comparedto females. Regression equations were derived from right and left foot length for estimating stature in malesand females. Stature (Y) could be calculated from the right foot length (X1) in males with the equation Y= 53.050 + 4.802 X1. For the left foot length (X2) in males, the equation was Y = 53.618 + 4.7762 X2. Infemales, the equations were Y = 78.538 + 3.597 X1 & Y = 78.724 + 3.601 X2 respectively.